Folklorni in živalski slovar v ustvarjalnem opusu Svetlane Makarovič - Golež Kaučič, Marjetka (Jezik in slovstvo, 2011)
The article deals with selected texts from the creative opus of the diverse works by Svetlana Makarovič and their link with Slovene folklore on the motivic-thematic level, with the use of folklore methods and by relating the identification of folklore elements to their interpretation, as well as on the intertextual level, with an analysis of the antecedents from folk poetry in the poet´s texts in terms of content, form and quotation. In addition to an in-depth analysis of three texts and the detection of bestiary in Makarovič´s poetry, the article also uses the concepts of zoo folklore, animal culture and ecocriticism. The first subject of analysis is the dramatic text Mrtvec pride po ljubico (1982), based on the ballad from folk mythology with the same title, which, integrated into a new poetic and genre text, establishes a dialogue with tradition, while at the same time the original text undergoes manifold creative "deformations" and gains new conceptual and semantic dimensions. The article then turns to an analysis of the meta-text Katalena (2009), a contemporary narrative text that has the family ballad Z roparjem omožena as a prototext, which it approaches in terms of the essence of the content, while departing from it in genre and in the treatment of the story. The third text, the radio play Živali pokopavajo lovca (2002), is a transformation of the folk animal ballad Lovčev pogreb, in which Makarovič introduces the folk poem in her syncretic image of the text and of melody, while also adding her own conceptual and semantic emphases. This text can also be read as an ecocritical text.
Keywords: Makarovič, Svetlana, 1939-; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija; folkloristics; slovenske pesnice; folkloristika; zoofolkloristika